The Role of Online Queues as a Moderator Between Service Quality and Patient Satisfaction for National Health Insurance's Participants - Adhe Sugi Windarini Ni Made; Landra Nengah; Gunadi I Gusti Ngurah Bagus (AIBPM Publisher, 2024)
This study aims to provide new insight and fill the gap of previous research by adding online queues to moderate the effect of perceived service quality and the organization’s image on perceived satisfaction. Data were collected from 120 respondents who are members of National Health Insurance (JKN) who became patients at Prof. dr. I Goesti Ngoerah Gde Ngoerah Hospital Denpasar. Partial Least Square Structural Equation Modeling (PLS-SEM) was used to analyze and test hypotheses. This research applied quantitative approach using a pre-existing measurement scale. The results of this study prove that service quality has a positive and significant effect on customer satisfaction. Another finding from this study is that an organization's image does not significantly affect customer satisfaction. Online queues could not moderate the relationship between service quality and the organization's image on customer satisfaction. The practical implication of this research is that hospitals must continue to improve the quality of their services to increase patient satisfaction with the hospital.